A Modest Proposal to Move RCR Education Out of the Classroom and into Research - Michael Kalichman (American Society for Microbiology, 2014)
Requirements for training in responsible conduct of research have significantly increased over the past 25 years, but worries about the integrity of science have only intensified. The approach to training has relied largely on short-term experiences, either online or in person. Even if done well, such strategies remain separate from, and a negligible fraction of, the practice of research. A proposed alternative is to empower faculty, postdoctoral fellows, and graduate student leaders to foster conversations about research ethics in the research environment.